Regulation of Key Genes for Milk Fat Synthesis in Ruminants - Mu, Tong; Hu, Honghong; Ma, Yanfen; Feng, Xiaofang; Zhang, Juan; Gu, Yaling (Frontiers in Nutrition, 2021)
Milk fat is the main ingredient in the production of butter and yogurt, which plays an important role in human growth and development. It not only affects the flavor and nutritional value of milk, but is also the main target trait of ruminant breeding. There are many key genes involved in ruminant milk fat synthesis, including ACSS2, FASN, ACACA, CD36, ACSL, SLC27A, FABP3, SCD, GPAM, AGPAT, LPIN, DGAT1, PLIN2, XDH and BTN1A1. Taking the de novo synthesis of fatty acids (FA) and intaking of long-chain fatty acids (LCFA) in blood to the end of lipid droplet secretion as the mainline, this manuscript elucidates the complex regulation model of key genes in mammary epithelial cells (MECs) in ruminant milk fat synthesis, and constructs the whole regulatory network of milk fat synthesis, to provide valuable theoretical basis and research ideas for the study of milk fat regulation mechanism of ruminants.